Robust Detection of Malicious Nodes in Mobile Sensor Networks Using Software Attestation - Jun-Won Ho (International Journal of Distributed Sensor Networks)
In ad hoc and sensor networks, reputation-based trust management schemes have been widely used to identify the malicious nodes. These schemes leverage each node's behaviors for malicious node detection and thus require a certain amount of time to observe the behaviors of nodes. In mobile sensor networks, however, malicious nodes frequently move to different locations, and thus it is likely difficult to collect enough evidence for them. Moreover, when reputation-based schemes are employed, it is not easy to revoke the malicious nodes due to the risk of false positives. To mitigate these limitations of reputation-based schemes, we propose mobile malicious node detection schemes based on software attestation technique, which virtually fulfills zero false positives. In particular, we propose a probabilistic detection scheme in which each node attests its neighboring node with a certain probability. In order to reduce the attestation overhead of the probabilistic detection scheme, we also propose the SPRT (Sequential Probability Ratio Test) based detection scheme that uses the SPRT to determine when to perform the attestations. Through analysis and simulation, we show that our proposed schemes detect mobile malicious nodes through software attestations in robust and efficient manner.